Peningkatan Hasil Belajar Bahasa Inggris Materi Introduction melalui Model Problem Based Learning pada Siswa Kelas VII SMP - Andi Febryna; Rahmadian Rahmadian (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2026)
The primary objective of this research is to enhance English academic proficiency among seventh-grade pupils at UPT SMP Negeri 4 Takalar, specifically regarding "Introduction" subject matter, through the application of the Problem-Based Learning (PBL) framework. This study was necessitated by observed deficiencies in student engagement and challenges in vocabulary acquisition, particularly concerning regular and irregular verbs, which had previously led to unsatisfactory academic performance. Utilizing a Classroom Action Research (CAR) design, the investigation was executed over two distinct cycles with a cohort of 24 students from Class VII B. Data acquisition involved the administration of performance assessments and systematic classroom observations. Subsequent analysis revealed a marked enhancement in learning achievements. During Cycle I, the mean score was recorded at 78.75, corresponding to a classical mastery rate of 37.5%. Following instructional refinements in Cycle II, the average score rose to 80.42, while the classical mastery rate increased to 50%. Moreover, observational evidence highlighted constructive behavioral shifts characterized by heightened engagement in collaborative discussions and improved oral communication confidence. Consequently, this study concludes that deploying the PBL model serves as an effective strategy for augmenting both English academic achievement and social interaction within the classroom environment.